Preparation and characterization of high-density polyethylene-reinforced flax straw fibers for use as biocomposite panels - Ali A. M. Yassene; Hussein E. Ali; Ahmed Awadallah-F (Journal of Materials Science: Materials in Engineering)
Abstract The increasing demand for sustainable and eco-friendly materials has driven research into developing biocomposites as alternatives to conventional plastics. This study addresses the challenge of optimizing the properties of biocomposite panels made from high-density polyethylene (HDPE) and short flax straw fibers (FSF) at low content ratios. The aim of the study was to fabricate and characterize biocomposite panels to evaluate their potential for large-scale production. A comprehensive methodology was employed, including the use of Fourier transform infrared (FTIR), thermogravimetric and derivative thermal gravimetric (TGA-DTG), mechanical property testing, differential scanning calorimetry (DSC), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), X-ray diffraction (XRD), water contact angle measurements, ultrasonic testing, water absorption (WA) analysis, and chemical resistance evaluation. Remarkable results revealed that graft copolymerization occurred between HDPE and FSF, as confirmed by FTIR, while SEM indicated the successful incorporation of FSF into the HDPE matrix. The mechanical properties, including tensile strength, elastic modulus, and elongation, were significantly influenced by the presence of FSF. Thermal stability decreased slightly with the addition of FSF, and DSC analysis showed a minor shift in the melting point. Water contact angle values increased with higher FSF content, while XRD results indicated a reduction in HDPE intensity. Water absorption increased with higher FSF content, suggesting a trade-off between fiber content and hydrophobicity. The significance of this study lies in demonstrating that these biocomposite panels exhibit promising properties for large-scale production, offering a sustainable alternative to traditional composites in various industrial applications.